Novel Medical and General Hebrew Terminology from the Middle Ages : Volume 8 - Bos, Gerrit (Middle East and Islamic Studies E-Books Online, Collection 2025., 2026)
This volume is a continuation of the seven already published titles in the series (2011-2024) and further pursues the mapping of medical terminology featuring in medieval Hebrew medical works in order to facilitate study of medical terms that do not appear in the existing dictionaries, as well as identifying the medical terminology used by specific authors and translators in order to identify anonymous medical material. The Hebrew terminology discussed in this volume has been derived from six different sources, namely translations of Guy de Chauliac's Inventarium sive Chirurgia Magna, Bernard de Gordon's Lilium Medicinae, and Ibn Sīnā's K. al-Qānūn.